ChemInform Abstract: Bi3n+1Ti7Fe3n‐3O9n+11 Homologous Series: Slicing Perovskite Structure with Planar Interfaces Containing Anatase‐Like Chains. Issue 16 (March 2016) - Batuk, Dmitry; Tsirlin, Alexander A.; Filimonov, Dmitry S.; Zakharov, Konstantin V.; Volkova, Olga S.; Vasiliev, Alexander; Hadermann, Joke; Abakumov, Artem M.
Abstract: Title compounds with n = 3—6 are prepared by solid state reaction of Bi2 O3, TiO2, and Fe2 O3 (1000 °C, 60—100 h).